A Series of Green Light Absorbing Organic Photosensitizers Capable of Oxidative Quenching Photocatalysis. Issue 1 (10th September 2020) - Bobo, M. Victoria; Arcidiacono, Ashley M.; Ayare, Pooja J.; Reed, Jordan C.; Helton, Maizie R.; Ngo, Thi; Hanson, Kenneth; Vannucci, Aaron K.
Abstract: In order to design a series of photoredox compounds with a broad range of reactivity, eosin Y, a xanthene derivative, was chosen as a precursor to synthesize a new series of organic photocatalysts. The synthesis and characterization of these four new organic photocatalysts was undertaken. Redox potentials of this series of photocatalysts varied by 110 mV, which shows that these catalysts can be tuned for specific reactions. The measured fluorescence quantum yields ranged from 0.33 to 0.65 which outperform most transition metal photocatalysts. The excited state lifetimes (ns) of the new photocatalysts are comparable to those of the parent complex, but the λmax  value for absorption was red‐shifted into the green light region of the solar spectrum. Despite the absorbance shift to lower energy wavelengths, the new photocatalysts were more potent reductants compared to the parent complex and were able to undergo oxidative quenching and promote the photocatalytic enol arylation reaction. Abstract : Go green : A series of four photocatalysts were synthesized as derivatives of the xanthene‐based eosin Y photocatalyst. The new compounds exhibit green‐light absorption, yet are potent excited‐state reductants capable of undergoing oxidative quenching photocatalysis.